2018
DOI: 10.15761/gdt.1000149
|View full text |Cite
|
Sign up to set email alerts
|

Effects of lactoferrin on dexamethasone-induced osteoporosis in mice

Abstract: Materials and methods MaterialsBovine LF was supplied by NRL Pharma, Inc. (Kanagawa, Japan). Dexamethasone sodium phosphate (DEX) was purchased from Wako Pure Chemical Industries, Ltd. (Osaka, Japan). All other chemicals were obtained commercially at the purest grade available. Animals and experimental proceduresForty-eight 7-week-old male ICR mice (Japan SLC Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…Furthermore, osterix regulates osteocalcin involvement in calcification [ 24 ]. These results, supported previous studies which bovine LF improved osteogenic marker genes in vivo and in vitro, suggest that LF-II can affect osterix expression and enhance calcification after 2–8 h, demonstrating that human recombinant LF has similar effects as bovine LF [ 11 , 12 , 13 , 17 ].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Furthermore, osterix regulates osteocalcin involvement in calcification [ 24 ]. These results, supported previous studies which bovine LF improved osteogenic marker genes in vivo and in vitro, suggest that LF-II can affect osterix expression and enhance calcification after 2–8 h, demonstrating that human recombinant LF has similar effects as bovine LF [ 11 , 12 , 13 , 17 ].…”
Section: Discussionsupporting
confidence: 89%
“…MC3T3-E1 cells were seeded at a density of 1 × 10 4 cells/well in 96-well plates and cultured in α-MEM supplemented with 10% FBS. After incubation for 1 d, the growth medium was changed to include 100 μg/mL LF (IF-I and LF-II) with or without 50 μg/mL ascorbic acid and 10 mM β-glycerophosphate (β-GP), then incubated for 24 h. Concentration of LF were determined according to previous studies [ 17 ]. The 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay was performed using a CellQuanti-MTT cell viability assay kit (BioAssay Systems, CA, USA), and absorbance was measured at 570 nm.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…After oral administration for the first 2 weeks, all mice were intraperitoneally injected with DEX (15 mg/kg/day). Many studies have reported that 2 weeks to 1 month of DEX treatment results in muscle atrophy or bone loss in mice and rats [ [29] , [30] , [31] , [32] , [33] , [34] , [35] ]. We induced both muscle atrophy and bone loss by intraperitoneally injecting DEX for 1 month.…”
Section: Methodsmentioning
confidence: 99%